Em busca dos sentimentos morais: do desenvolvimento das emoções básicas ao papel das emoções morais complexas nos processos de julgamento - Marques, Lucas Murrins (2020)
The study of emotions presents relevant growth. Among the emotional categories, it is understood moral emotion, by a set of physiological changes and/or cognitive processing that present as a consequence the establishment and maintenance of the integrity of human social structures. More recently, the role of intuitions, triggers, or moral foundations that would guide judgment, have been widely discussed: i) Care; ii) Justice; iii) Liberty; iv) Authority; v) Loyalty; and vi) Purity. In addition, some studies demonstrate the role of some aspects in the relationship and modulation of moral judgments, such as: i) cultural variations; ii) basic emotional processing; iii) social categorization; iv) development; v) emotion regulation; and vi) the role of brain processing in moral judgment. Despite these findings, many gaps are still present in this study topic. Thus, through six studies, this thesis aimed to describe, correlate and modulate the interface between emotions and judgment. For this, each Study presents particularities in the general and specific objectives, methods, and casuistic, all being duly justified and directly related to the general objective of the present thesis. Specifically, the objectives of each Study were: Study 1) To translate, adapt and validate an instrument of judgment of the different moral foundations for the population of the city of São Paulo; Study 2) Investigate the effects of the modulation of the basic emotion of Disgust on moral judgment relative to different social groups; Study 3) Investigate the role of perception of Group Categories of Authors and Victims in situations of violation of the Care Foundation; Study 4) Investigate and correlate moral judgment at different ages and sex; Study 5) Investigate the effects of emotion regulation on moral judgment; and Study 6) Investigate the effects of Neuromodulation of Prefrontal Cortex on moral judgment. At the heart of this thesis, some studies will involve current crisis scenarios and discussions (eg, local and global conflicts regarding different cultures, sexes, and social groups). Thus, in addition to deriving contributions to the theoretical field between emotions and moral judgment, the results may contribute to discussions about social phenomena in the field of moral sciences in contemporary and crisis scenarios.